KORELASI ANTARA PENERAPAN PENDEKATAN KONSTRUKTIVISME DENGAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH MATEMATIKA DASAR (Jurnal Pelangi : Research of Education and Development, 2022)
The purpose of this research is to get information about correlation between constructivismapproach with student learning outcomes in basic mathematics lectures. This research uses a descriptive method. Participants in this study are biology education students who take the basic mathematics courses amounting to 28 people. The result of this research shows that there is a significance correlation between the constructivism approach with student learning outcomes in basic mathematics lectures.  Keywords: Constructivism Approach, Student Learning Outcomes, Basic Mathematics Lectures